A mHealth Support Program for Australian Young Adults with Type 1 Diabetes: A Mixed Methods Study. (October 2019) - Ng, Ashley H; Crowe, Timothy C; Ball, Kylie; Rasmussen, Bodil
Aims and Objectives: Young adulthood is a life stage comprised of many turning points. For young adults with type 1 diabetes (T1DM), diabetes self-management support is crucial during this period. There is a lack of diabetes education programs and services tailored to this population. This paper presents the findings, according to the STROBE guidelines, on the usability and acceptability of a patient-informed mHealth support program (Diabetes YES) that was developed for young adults with T1DM. Methods: A total of 34 young adults aged 18–35 years with T1DM participated in the Diabetes YES program over 12 weeks. Google analytics was used to tracked website use, while a website usability survey measured ease of use. Facebook analytics was used to measure peer support engagement. Evaluation of the program was completed using Likert scales and open-ended questions. Results: Participants rated the website favourably for its ease of navigation and easy to understand information. Web page visits declined sharply while peer support group engagement through Facebook remained consistent throughout the intervention period. Participants utilised weekly discussion topics to generate conversation within the peer support group. Emotional support from peers was the highest regarded benefit reported by participants. Conclusions: Diabetes YES is an example of an mHealth support program that was readily accepted by young adults living with T1DM. Feasibility studies are an important formative step in the implementation of mHealth programs within mainstream healthcare. Future work should focus on the adaptability of such programs to fit within larger consumer or healthcare organisations.